Islet of Langerhans transplantation. A comparative study of two different methods for isolating islet cells from rat pancreas - Spadella, Cesar Tadeu [UNESP]; Breim, Luis Carlos [UNESP]; Mercadante, Maria Cecília [UNESP]; Macedo, Célia Sperandéo de [UNESP]; Macedo, Arthur Roquete de [UNESP] (My University, 1997)
Two different methods for isolation of islet of Langerhans on control of metabolic abnormalities of alloxan-induced diabetic rat were tested. Sixty rats were randomly assigned to four experimental groups: GI included 10 non-diabetic control rats, GII included 10 diabetic control rats, without treatment, GIII included 20 diabetic rats (10 inbred and 10 outbred rats) that received islet of Langerhans transplantation (ILT) using islet cells prepared by collagenase, and GIV included 20 diabetic rats (10 inbred and 10 outbred rats) submitted to ILT using islet cells prepared by nonenzymatic method. Clinical and laboratory parameters at beginning and 4, 7, 14, 21 and 30 days of follow-up were recorded. Outbred rats were immunosuppressed with cyclosporin A, diabetes was induced by e.v. alloxan administration, and islet cells were isolated from normal donor Lewis rats and injected into the portal vein. ILT corrected the body weight gain, polyuria, polydipsia, polyphagia, and the high levels of blood and urine glucose in 73.7% of rats treated by enzymatic method and in 64.7% of those ones treated by nonenzymatic method. However, there was no significantly difference between the two methods (P > 0.50). We did not also observe significantly difference between the two methods when ILT was performed either in inbred or outbred rats. We concluded that ILT performed by nonenzymatic method may be an alternative treatment for diabetes due to be less expensive and to have possible advantages in the isolation process.